Time-effective strategies for the fabrication of poly- and single-crystalline gold nano-structures by focused helium ion beam milling. (25th March 2019) - Laible, Florian; Dreser, Christoph; Kern, Dieter P; Fleischer, Monika
Abstract: Milling with the focused helium ion beam of a helium ion microscope is one of the most accurate ways to produce nano-structures such as plasmonic nanoantennas. In addition to good and immediate control of the dimensions, features in the sub-10 nm regime are achievable. Especially small gaps and sharp tips in this regime may lead to very high field enhancement under excitation. However, the milling rate of 30 keV helium ions is rather low, making it time-consuming to cut nano-structures out of a gold film. We present two processes to work around the low milling rate to obtain arrays of nano-structures with maximum precision within a reasonable time. These strategies can both be adapted to either poly-crystalline gold films or single-crystalline gold flakes. Using single crystals from a fabrication point of view enables even higher precision due to constant etch rates over the whole crystal as well as straight edges and vertical side-walls due to the uniform crystalline structure.